Resin composition
The resin composition addresses the issue of insufficient curing and light-shielding in self-luminous displays by using a specific photoinitiator and black pigment, ensuring deep film curing and effective light-blocking, enhancing image quality in QD-OLED and micro LED displays.
Patent Information
- Application Number
- JP2021537283
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-07
- Filing Date
- 2020-07-31
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-07-31
AI Technical Summary
Conventional colored photosensitive resin compositions for self-luminous displays have low transmittance of incident light during exposure, leading to insufficient curing and poor light-shielding properties, which affects pattern formation and image quality in displays like QD-OLED and micro LED displays.
A resin composition comprising an alkali-soluble copolymer, a compound with multiple polymerizable groups, a photoinitiator with a high extinction coefficient, a black pigment, and a liquid repellent component, which allows for high transmittance of UV rays during exposure and effective curing, resulting in a film with high visible light-blocking properties.
The composition enables sufficient curing deep into the film, forming patterns with excellent visible light-shielding properties, improving image quality in self-luminous displays by serving as partition walls in wavelength conversion layers.
Smart Images

Figure 0007619265000001 
Figure 0007619265000002 
Figure 0007619265000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a photosensitive resin composition, more particularly to a resin composition suitable as a material for self-luminous displays such as quantum dot-organic electroluminescence (QD-OLED) displays and micro LED displays. [Background technology]
[0002] Self-luminous displays such as QD-OLED displays and micro LED displays are based on next-generation display technology that uses a blue self-luminous device as a base and implements red and green wavelength conversion layers using an inkjet printing method. This technology is highly regarded for its high color reproducibility and ability to express richer colors.
[0003] In the above-mentioned self-luminous display, in order to further improve the image quality, the use of colored partitions (colored liquid-repellent banks) with light-shielding properties for the partitions constituting the subpixels of the wavelength conversion layer of the display panel has been considered. However, in the conventional colored photosensitive resin composition, the transmittance of the incident light in the exposure process for partition formation is low, so that the film cannot be sufficiently cured deep inside, resulting in defective pattern formation. On the other hand, when priority is given to the curing of the film, it is difficult to ensure the necessary light-shielding properties due to insufficient addition of colorant.
[0004] Prior art documents related to the present invention include the following: [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 060240 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a resin composition which has good curability in an exposure step even in a colored state, is capable of forming a pattern, and gives a cured film having high visible light-shielding properties after curing. [Means for solving the problem]
[0007] As a result of extensive investigations to achieve the above-mentioned object, the present inventors have found that a resin composition using a photoinitiator having a specific absorption coefficient (in the present invention, this means a gram absorption coefficient; the same applies hereinafter) as a photoinitiator in combination with a specific black pigment is capable of forming a pattern, has a relatively high transmittance of ultraviolet light in an exposure step, can be sufficiently cured deep into the film, and further, can form a cured film with high visible light blocking properties by curing the composition, thereby completing the present invention.
[0008] That is, the present invention provides the following resin composition. 1. (A) an alkali-soluble copolymer; (B) a compound having two or more polymerizable groups of at least one type selected from the group consisting of an acrylate group, a methacrylate group, a vinyl group, and an allyl group; (C) photoinitiator: (C-1) a photoinitiator having an oxime ester group and having an absorption coefficient of 5,000 ml / g cm or more at 365 nm in methanol or acetonitrile; (D) black pigment: a black pigment comprising components (A), (B), (C-1), (C-2) and a photoinitiator having an absorption coefficient of 100 ml / g cm or less at 365 nm in methanol or acetonitrile; (D) a black pigment; (E) a liquid-repellent component, (F) a solvent and (G) a thiol compound, the black pigment being such that, in a 10 μm-thick thin film formed by coating a glass substrate with a dispersion of 10 parts by mass of component (D) dispersed in component (F) at a ratio of 10 parts by mass to 100 parts by mass of component (A) and drying the resulting film, the T1 / T2 value being 0.3 or more, where T1 is the light transmittance at a wavelength of 365 nm and T2 is the light transmittance at a wavelength of 550 nm; (E) a liquid repellent component, and (F) Solvent A resin composition comprising: 2. The resin composition of 1, wherein the content of the (D) component is 1 to 50 parts by mass per 100 parts by mass of the (A) component. 3. The resin composition of 1 or 2, wherein the number average molecular weight of component (A) is 2,000 to 50,000 in terms of polystyrene. 4. The resin composition according to any one of claims 1 to 3, wherein the component (A) is a copolymer of a monomer mixture containing at least one member selected from the group consisting of acrylic acid, methacrylic acid, maleic anhydride and maleimide. 5. Any of the resin compositions of 1 to 4, wherein the content of the component (C-1) is 0.3 to 5 parts by mass per 100 parts by mass of the component (A). 6. The resin composition of any one of 1 to 5, wherein the content of the component (B) is 10 to 150 parts by mass per 100 parts by mass of the component (A). 7. The resin composition according to any one of 1 to 6, wherein the component (C-1) is a photoinitiator having a carbazole structure. 8. A cured film obtained from any one of the resin compositions 1 to 7. 9. A partition wall for a self-luminous display formed from the resin composition according to any one of 1 to 7. 10. Wavelength conversion layer of a self-luminous display with 9 partitions. 11. An organic electroluminescent device having a wavelength conversion layer 10. 12. A microLED device with 10 wavelength conversion layers. Effect of the Invention
[0009] The resin composition according to the present invention has a relatively high transmittance of ultraviolet light in the exposure step, can be sufficiently cured deep into the film, and can form a cured film with high visible light blocking properties by curing the composition. The obtained cured film can be suitably used as a material for self-luminous displays such as QD-OLED displays and micro LED displays, and in particular, can be patterned and used as a partition (colored partition) constituting a subpixel of a wavelength conversion layer of a self-luminous display panel, thereby contributing to further improvement of the image quality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The resin composition of the present invention comprises (A) an alkali-soluble copolymer; (B) a compound having two or more polymerizable groups of at least one type selected from the group consisting of an acrylate group, a methacrylate group, a vinyl group, and an allyl group; (C) Photoinitiator: (C-1) a photoinitiator having an oxime ester group and an absorption coefficient in methanol or acetonitrile at 365 nm of 5,000 ml / g cm or more; (D) black pigment: a black pigment comprising components (A), (B), (C-1), (C-2) a photoinitiator having an absorption coefficient in methanol or acetonitrile of 100 ml / g cm or less at 365 nm, (D) a black pigment, (E) a liquid-repellent component, (F) a solvent, and (G) a thiol compound, the black pigment having a T1 / T2 value of 0.3 or more in a thin film having a thickness of 10 μm obtained by applying a dispersion obtained by dispersing 10 parts by mass of component (D) in component (F) to 100 parts by mass of component (A) on a glass substrate and drying the resulting film, where T1 is the light transmittance at a wavelength of 365 nm and T2 is the light transmittance at a wavelength of 550 nm; (E) a liquid repellent component, and (F) Solvent The resin composition contains:
[0011] <Component (A)> The alkali-soluble copolymer (A) is a copolymer obtained by copolymerization of a monomer mixture containing a monomer having an alkali-soluble group and other monomers (hereinafter, sometimes referred to as "copolymer of component (A)").
[0012] The copolymer of component (A) may be any copolymer that contains a structure having an alkali-soluble group in its repeating unit, and there are no particular limitations on the type of main chain skeleton and side chains of the polymer constituting the copolymer.
[0013] Taking into consideration the developability (solubility in an alkaline solution) of the unexposed areas, the number average molecular weight Mn of the copolymer of component (A) is preferably 2,000 to 50,000, and more preferably 5,000 to 20,000. In the present invention, the number average molecular weight Mn and the weight average molecular weight Mw described below are both values calculated as polystyrene by gel permeation chromatography (GPC).
[0014] Examples of the alkali-soluble group contained in the monomer having an alkali-soluble group include a carboxy group, a phenolic hydroxy group, an acid anhydride group, and a maleimide group.
[0015] Examples of monomers having a carboxy group include acrylic acid, methacrylic acid, crotonic acid, mono-(2-(acryloyloxy)ethyl)phthalate, mono-(2-(methacryloyloxy)ethyl)phthalate, N-(carboxyphenyl)maleimide, N-(carboxyphenyl)methacrylamide, N-(carboxyphenyl)acrylamide, and 4-vinylbenzoic acid.
[0016] Examples of monomers having a phenolic hydroxy group include hydroxystyrene, N-(hydroxyphenyl)acrylamide, N-(hydroxyphenyl)methacrylamide, and N-(hydroxyphenyl)maleimide.
[0017] Monomers having an acid anhydride group include, for example, maleic anhydride and itaconic anhydride.
[0018] Examples of monomers having a maleimide group include maleimide, the above-mentioned N-(carboxyphenyl)maleimide, and N-(hydroxyphenyl)maleimide.
[0019] In the present invention, among these monomers having an alkali-soluble group, a copolymer of a monomer mixture containing at least one selected from the group consisting of acrylic acid, methacrylic acid, maleic anhydride, and maleimide is preferred.
[0020] In the present invention, when obtaining the copolymer, another monomer copolymerizable with the monomer having an alkali-soluble group is used in combination. Examples of the other monomers include acrylic acid ester compounds, methacrylic acid ester compounds, N-substituted maleimide compounds, acrylonitrile compounds, acrylamide compounds, methacrylamide compounds, styrene compounds, and vinyl compounds.
[0021] Examples of the acrylic acid ester compound include methyl acrylate, ethyl acrylate, isopropyl acrylate, benzyl acrylate, naphthyl acrylate, anthryl acrylate, anthryl methyl acrylate, phenyl acrylate, phenoxyethyl acrylate, 2,2,2-trifluoroethyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, isobornyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, tetrahydrofurfuryl acrylate, 3-methoxybutyl acrylate, and 2-methyl-2-adamantyl acrylate. acrylate, 2-propyl-2-adamantyl acrylate, 8-methyl-8-tricyclodecyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 2,3-dihydroxypropyl acrylate, diethylene glycol monoacrylate, caprolactone 2-(acryloyloxy)ethyl ester, poly(ethylene glycol) ethyl ether acrylate, 5-acryloyloxy-6-hydroxynorbornene-2-carboxylic-6-lactone, acryloylethyl isocyanate, 8-ethyl-8-tricyclodecyl acrylate, and glycidyl acrylate.
[0022] Examples of the methacrylic acid ester compounds include methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, benzyl methacrylate, naphthyl methacrylate, anthryl methacrylate, anthryl methyl methacrylate, phenyl methacrylate, phenoxyethyl methacrylate, 2,2,2-trifluoroethyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, 2-methoxyethyl methacrylate, methoxytriethylene glycol methacrylate, 2-ethoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, 3-methoxybutyl methacrylate, 2-methyl-2-adamantyl methacrylate, γ- butyrolactone methacrylate, 2-propyl-2-adamantyl methacrylate, 8-methyl-8-tricyclodecyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 2,3-dihydroxypropyl methacrylate, diethylene glycol monomethacrylate, caprolactone 2-(methacryloyloxy)ethyl ester, poly(ethylene glycol) ethyl ether methacrylate, 5-methacryloyloxy-6-hydroxynorbornene-2-carboxylic-6-lactone, methacryloylethyl isocyanate, 8-ethyl-8-tricyclodecyl methacrylate and glycidyl methacrylate.
[0023] Examples of vinyl compounds include methyl vinyl ether, benzyl vinyl ether, vinyl naphthalene, vinyl anthracene, vinyl biphenyl, vinyl carbazole, 2-hydroxyethyl vinyl ether, phenyl vinyl ether, and propyl vinyl ether.
[0024] Examples of styrene compounds include styrene, methylstyrene, chlorostyrene, and bromostyrene.
[0025] Examples of N-substituted maleimide compounds include N-methylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide.
[0026] An example of the acrylonitrile compound is acrylonitrile.
[0027] Examples of acrylamide compounds include hydroxyacrylamide, N-methylacrylamide, N-ethylacrylamide, N-isopropylacrylamide, N-butylacrylamide, diacetone acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N,N-dipropylacrylamide, acrylloylmorpholine, Nn-butoxymethylacrylamide, N-isobutoxymethylacrylamide, and N-methoxymethylacrylamide.
[0028] Examples of methacrylamide compounds include hydroxymethacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, N-isopropylmethacrylamide, N-butylmethacrylamide, diacetonemethacrylamide, N,N-dimethylmethacrylamide, N,N-diethylmethacrylamide, N,N-dipropylmethacrylamide, 4-methacryloylmorpholine, Nn-butoxymethylmethacrylamide, N-isobutoxymethylmethacrylamide, and N-methoxymethylmethacrylamide.
[0029] In the present invention, among the above-mentioned other monomers, it is preferable to include at least one selected from the group consisting of an acrylic acid ester compound, a methacrylic acid ester compound, an N-substituted maleimide compound, an acrylonitrile compound, an acrylamide compound, a methacrylamide compound, a styrene compound, and a vinyl compound, and it is more preferable to include a methacrylic acid ester compound.
[0030] Among the above-mentioned monomers having an alkali-soluble group and other monomers, a combination of a monomer having a carboxy group and a methacrylic acid ester compound is more preferable, and a combination of methacrylic acid and methyl methacrylate is even more preferable.
[0031] The method for obtaining the copolymer of component (A) is not particularly limited, but for example, the copolymer can be obtained by polymerizing a monomer mixture containing the above-mentioned monomer having an alkali-soluble group and other monomers in a solvent at 50 to 110°C. The solvent can be used without particular limitations as long as it dissolves the monomer having an alkali-soluble group and other monomers, as well as the copolymer of component (A). Specific examples include the solvents exemplified in component (F) described below. In addition, it is preferable to use a known polymerization initiator such as azobisisobutyronitrile during polymerization.
[0032] The copolymer solution of component (A) obtained as above is poured into diethyl ether or water under stirring to cause reprecipitation, and the resulting precipitate is filtered and washed, and then dried at room temperature or by heating under normal or reduced pressure to obtain a powder of the copolymer. By such an operation, the polymerization initiator and unreacted monomers coexisting with the copolymer can be removed, and as a result, a purified copolymer powder can be obtained. If the copolymer cannot be sufficiently purified by one operation, the obtained powder can be redissolved in a solvent and the above operation can be repeated.
[0033] In the present invention, the polymerization solution of the alkali-soluble copolymer (A) may be used as it is, or a solution obtained by redissolving the isolated polymer powder in a suitable solvent may be used. Examples of the solvent include the solvents exemplified for the component (F) described below.
[0034] The mass ratio of the alkali-soluble monomer to the other monomer ([alkali-soluble monomer] / [other monomer]) is preferably 5 / 95 to 50 / 50, more preferably 10 / 90 to 30 / 70. By setting the mass ratio within the above range, good curability can be obtained in the exposed area, and good developability can be obtained in the unexposed area.
[0035] <(B) component> The component (B) is a compound having two or more polymerizable groups of at least one type selected from the group consisting of an acrylate group, a methacrylate group, a vinyl group, and an allyl group. In the present invention, the term "compound having two or more polymerizable groups" means a compound having two or more polymerizable groups in one molecule, and the polymerizable groups are located at the molecular terminals. The component (B) is preferably a compound having an Mw of 1,000 or less, from the viewpoints of having good compatibility with each component and not affecting developability.
[0036] Specific examples of the component (B) include dipentaerythritol hexaacrylate, dipentaerythritol hexamethacrylate, dipentaerythritol pentaacrylate, dipentaerythritol pentamethacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol diacrylate, pentaerythritol dimethacrylate, tetramethylolpropane tetraacrylate, tetramethylolpropane tetramethacrylate, tetramethylolmethane tetraacrylate, tetramethylolmethane tetramethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, 1,3,5-triacryloylhexahydro-S-triazine, 1,3,5-trimeth ... xahydro-S-triazine, tris(hydroxyethyl acryloyl)isocyanurate, tris(hydroxyethyl methacryloyl)isocyanurate, triacryloyl formal, trimethacryloyl formal, 1,6-hexanediol acrylate, 1,6-hexanediol methacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, ethanediol diacrylate, ethanediol dimethacrylate, 2-hydroxypropanediol diacrylate, 2-hydroxypropanediol dimethacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, isopropylene glycol diacrylate, isopropylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, N,N'-bis(acryloyl)cysteine, N,Examples of such compounds include N'-bis(methacryloyl)cysteine, thiodiglycol diacrylate, thiodiglycol dimethacrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol F diacrylate, bisphenol F dimethacrylate, bisphenol S diacrylate, bisphenol S dimethacrylate, bisphenoxyethanol fluorene diacrylate, bisphenoxyethanol fluorene dimethacrylate, diallyl ether bisphenol A, o-diallyl bisphenol A, diallyl maleate, and triallyl trimellitate. These compounds having two or more polymerizable groups can be used alone or in combination of two or more.
[0037] The above compounds can be obtained as commercially available products. Examples of such commercially available products include KAYARAD (registered trademark) T-1420, DPHA, DPHA-2C, D-310, D-330, DPCA-20, DPCA-30, DPCA-60, DPCA-120, DN-0075, DN-2475, R-526, NPGDA, PEG400DA, MANDA, and R-1. 67, HX-220, HX620, R-551, R-712, R-604, R-684, GPO-303, TMPTA, THE-330, TPA-320, TPA-330, PET-30, RP-1040 (manufactured by Nippon Kayaku Co., Ltd.); Aronix (registered trademark) M-210, M-208, M-211B, M-215, M-220, M-225, M-270, M-240, M-6100, M-6250, M-6500, M-6200, M-309, M-310, M-321, M-350, M-360, M-313, M-315, M- 306, M-303, M-452, M-408, M-403, M-400, M-402, M-405, M-406, M-450, M-460, M-510, M-520, M- 1100, M-1200, M-6100, M-6200, M-6250, M-6500, M-7100, M8030, M8060, M8100, M8530, M-8560, M 9050 (manufactured by Toagosei Co., Ltd.); Viscoat 295, 300, 360, GPT, 3PA, 400, 260, 312, 335HP, 700 (manufactured by Osaka Organic Chemical Industry Co., Ltd.);A-200, A-400, A-600, A-1000, A-B1206PE, ABE-300, A-BPE-10, A-BPE-20, A-BPE-30, A-BPE-4, A-BPEF, A-BPP-3, A-DCP, A-DOD- N, A-HD-N, A-NOD-N, APG-100, APG-200, APG-400, APG-700, A-PTMG-65, A-9300, A-9300-1CL, A-GLY-9E, A-GLY-20E, A-TMM-3, A- TMM-3L, A-TMM-3LM-N, A-TMPT, AD-TMP, ATM-35E, A-TMMT, A-9550, A-DPH, TMPT, 9PG, 701A, 1206PE, NPG, NOD-N, HD-N, DOD-N, DC P, BPE-1300N, BPE-900, BPE-200, BPE-100, BPE-80N, 23G, 14G, 9G, 4G, 3G, 2G, 1G (manufactured by Shin Nakamura Chemical Co., Ltd.); Light Ester EG, 2EG, 3EG, 4E G, 9EG, 14EG, 1.4BG, NP, 1.6HX, 1.9ND, G-101P, G-201P, DCP-M, BP-2EMK, BP-4EM, BP-6EM, TMP, Light Acrylate 3EG-A, 4EG-A, 9EG-A, 14EG-A, PTMGA-250, NP-A, MPD-A, 1.6HX-A, 1.9ND-A, MOD-A, DCP-A, BP-4PA, BA-134, BP-10EA, H PP-A, G-201P, TMP-A, TMP-3EO-A, TMP-6EO-3A, PE-3A, PE-4A, DPE-6A, Epoxy Ester 40EM, 70PA, 200PA, 80MFA, 3002M, 3002A, 3000MK, 3000A, EX-0205, AH-600, AT-600, UA-306H, UA-306T, UA-306I, UA-510H, UF-8001G, DAUA-167 (manufactured by Kyoeisha Chemical Co., Ltd.);EBECRYL® TPGDA, 145, 150, PEG400DA, 11, HPNDA, PETIA, PETRA, TMPTA, TMPEOTA, OTA480, DPHA, 180, 40, 140, 204, 205, 210, 215, 220, 6202, 230, 244, 245, 264, 265, 270, 280 / 15IB, 284, 285, 294 / 25HD, 1259, KRM8200, 4820, 4858, 512 9, 8210, 8301, 8307, 8402, 8405, 8411, 8804, 8807, 9260, 9270, KRM7735, KRM8296, KRM8452, 8311, 8701, 9227EA, 80, 436, 438, 446, 450, 505, 524, 525, 770, 800, 810, 811, 812, 1830, 846, 851, 852, 853, 1870, 884, 885, 600, 605, 645, 648, 860, 1606, 3500, 3608, 3700, 3701, 3702, 3703, 3708, and 6040 (manufactured by Daicel-Allnex Co., Ltd.); SR212, SR213, SR230, SR238F, SR259, SR268, SR272, SR306H, SR344, SR349, SR508, CD560, CD561, CD564, SR601, SR602, SR610, SR833S, SR9003, CD9043, SR9045, SR9209, SR205, SR206, S R209, SR210, SR214, SR231, SR239, SR248, SR252, SR297, SR348, SR480, CD540, CD541, CD542, SR603, SR644, SR9036, SR351S, SR368, SR415, SR444, SR454, SR492, SR499, CD501, SR502, SR9020, CD9021, SR9035, SR350, SR295, SR355, SR399, SR494, and SR9041 (manufactured by Sartomer).
[0038] The content of the (B) component is preferably 10 to 150 parts by mass, more preferably 20 to 120 parts by mass, and even more preferably 30 to 110 parts by mass, relative to 100 parts by mass of the (A) component. By making the content of the (B) component equal to or greater than the lower limit of the above range, the exposed area can be sufficiently cured, and pattern formation can be performed reliably. In addition, by making the content of the (B) component equal to or less than the upper limit of the above range, tack does not occur in the coating film after prebaking, and good developability is ensured in the unexposed area.
[0039] <(C) component> The component (C) is a photoinitiator, and in the present invention, the following photoinitiator (C-1) having a specific absorption coefficient is used.
[0040] <(C-1) component> Component (C-1) is a photoinitiator that has an oxime ester group and an absorption coefficient in methanol or acetonitrile of 5,000 ml / g cm or more at 365 nm. Specifically, it is a compound that has an oxime ester group and a light absorbing site and has an absorption coefficient in methanol or acetonitrile of 5,000 ml / g cm or more at 365 nm.
[0041] An example of the oxime ester group is a group represented by the following formula (1).
[0042] [ka] (In the formula, R 1 represents a phenyl group, an alkyl group having 1 to 10 carbon atoms, or a benzyl group; R 2 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group, and the dashed line represents a bond.
[0043] The alkyl group having 1 to 10 carbon atoms may be linear, branched, or cyclic, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a cyclopropyl group, an n-butyl group, an isobutyl group, a s-butyl group, a t-butyl group, an n-pentyl group, a neopentyl group, a cyclopentyl group, an n-hexyl group, a cyclohexyl group, an n-octyl group, an n-decyl group, and a 1-adamantyl group.
[0044] The light absorbing site is preferably, for example, a group selected from a phenyl group, a phenylthiophenyl group, an N-alkylcarbazole group, a naphthyl group, a coumarin group, an alkoxyphenyl group, a phenylalkoxyphenyl group, and a phenoxyalkoxyphenyl group, substituted with a group having a benzoyl structure such as a benzoyl group or a naphthylcarbonyl group. Furthermore, the structure may be substituted with a phenyl group, a phenylthio group, a diphenylamino group, etc.
[0045] As the component (C-1), for example, a compound in which an oxime ester group represented by formula (1) is bonded via a single bond or a carbonyl group to a group selected from a phenyl group, a phenylthiophenyl group, an N-alkylcarbazole group, a naphthyl group, a coumarin group, an alkoxyphenyl group, a phenylalkoxyphenyl group, and a phenoxyalkoxyphenyl group at a light absorbing site is preferred. Among these, in the present invention, those having a carbazole structure are preferred.
[0046] Specific examples of the (C-1) component include 1-(4-phenylthiophenyl)-1,2-octanedione-2-(O-benzoyloxime), ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), (E)-4-(4(4-(diphenylamino)benzoyl)benzyloxy)benzaldehyde-O-acetyloxime, (E)-4-(4,8-dimethoxy-1-naphthoyl)benzaldehyde-O-acetyloxime, 1-(9-propyl-9H-carbazol-3-yl)butane-1,3-dione-1-(O-acetyloxime), and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]butane-1,3-dione-1-(O-acetyloxime).
[0047] The (C-1) component is readily available as a commercially available product, and examples of such commercially available products include IRGACURE (registered trademark) OXE01, IRGACURE (registered trademark) OXE02, and IRGACURE (registered trademark) OXE03 (all manufactured by BASF), ADEKA Optomer N-1919, ADEKA Arcles NCI-831, and ADEKA Arcles NCI-930 (all manufactured by ADEKA Corporation). These (C-1) components may be used alone or in combination of two or more types.
[0048] The content of the (C-1) component is preferably 0.3 to 5 parts by mass, and more preferably 0.5 to 4 parts by mass, per 100 parts by mass of the (A) component. By keeping the content of the (C-1) component within the above range, good curability can be obtained.
[0049] <(C-2) component> In the present invention, component (C-1) may be used in combination with (C-2), a photoinitiator having an absorption coefficient of 100 ml / g cm or less in methanol or acetonitrile at 365 nm. By using two photoinitiators with different absorption coefficients as component (C), it is possible to further improve curability and developability. As component (C-2), for example, one having a hydroxy group is preferred.
[0050] Specific examples of the (C-2) component include 1-hydroxy-cyclohexyl-phenyl-ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, phenylglyoxylic acid methyl ester, and 2-oxy-2-phenylacetic acid 2-[2-hydroxy-ethoxy]ethyl ester.
[0051] The (C-2) component is readily available as a commercially available product, and examples of such commercially available products include IRGACURE (registered trademark) 2959, IRGACURE (registered trademark) 754, IRGACURE (registered trademark) 184, DAROCURE MBF, and DAROCURE 1173 (all manufactured by BASF). These (C-2) components may be used alone or in combination of two or more.
[0052] When the (C-2) component is used, its content is preferably 0.5 to 10 parts by mass, more preferably 1 to 7 parts by mass, based on 100 parts by mass of the (A) component. By making the content of the (C-2) component equal to or higher than the lower limit of the above range, good curability can be obtained. By making the content of the (C-2) component equal to or lower than the upper limit of the above range, good developability can be ensured in the unexposed areas.
[0053] <(D) component> The component (D) is a black pigment that contains the components (A), (B), (C-1), (C-2), (D), (E) a liquid-repellent component, (F) a solvent, and (G) a thiol compound, and is dispersed in the component (F) at a ratio of 10 parts by mass of the component (D) to 100 parts by mass of the component (A). The dispersion is applied to a glass substrate, and dried to form a thin film having a thickness of 10 μm. When the light transmittance at a wavelength of 365 nm is T1 and the light transmittance at a wavelength of 550 nm is T2, the T1 / T2 value is 0.3 or more. In the dispersion, the types of the components (A) and (D), and the types and contents of the components other than the components (A) and (D) can be the same as those described in the above-mentioned components (A) to (C) and the below-mentioned components (D) to (G). As the solvent used in the dispersion, propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate are suitable. These solvents may be used alone or in combination of two or more.
[0054] In consideration of the ultraviolet light transmittance and visible light shielding ability, the (D) component is preferably one having the above T1 / T2 value of 1.0 or more, more preferably one having 1.5 or more. The upper limit of the T1 / T2 value is not particularly limited, but is generally preferably 5.0 or less, more preferably 3.0 or less. By using the (D) component having a T1 / T2 value within the above range, both the ultraviolet light transmittance in the exposure step and the visible light shielding ability of the obtained cured product are achieved.
[0055] Specific examples of the (D) component include zirconium nitride, titanium nitride, and titanium oxynitride, as well as mixtures thereof such as a mixed powder containing zirconium nitride and titanium nitride, and a mixed powder containing zirconium nitride and titanium oxynitride. In the present invention, zirconium nitride can be preferably used.
[0056] The purity of the zirconium nitride, titanium nitride and titanium oxynitride is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 90 mass % or more, more preferably 95 mass % or more, and even more preferably 98 mass % or more.
[0057] The zirconium nitride has a specific surface area of 20 to 90 m2 as measured by the BET method. 2 / g, and 30 to 60m 2 It is more preferable that the specific surface area of the titanium nitride and titanium oxynitride as measured by the BET method is 10 to 90 m 2 When the specific surface area is within the above range, the composition is less likely to settle during long-term storage, and the resulting cured film has good visible light shielding properties.
[0058] As such a black pigment, a commercially available product can be used, for example, NITRBLACK UB-1 (manufactured by Mitsubishi Materials Corporation). In addition, as a mixed powder containing zirconium nitride and titanium nitride, and a mixed powder containing zirconium nitride and titanium oxynitride, a mixed powder for forming a black film disclosed in JP2018-83730A can be mentioned.
[0059] The content of the component (D) is preferably 1 to 50 parts by mass, and more preferably 5 to 30 parts by mass, per 100 parts by mass of the component (A). By setting the content of the component (D) within the above range, both the ultraviolet ray transmittance in the exposure step and the visible light shielding ability of the obtained cured film can be achieved.
[0060] In addition, when preparing the composition, the (D) component may be mixed as a powder, but in order to obtain a more uniform composition, it is preferable to prepare a dispersion in which the (D) component is dispersed in a suitable solvent in advance. Specific examples of the solvent include the solvents described in the (F) solvent section below. When preparing the dispersion of the (D) component, a known dispersant may be used as necessary. As the dispersant, a commercially available product may be used, and an example of the dispersant may be Solsperse 34750 (manufactured by Lubrizol Japan Co., Ltd.).
[0061] <(E) component: liquid repellent component> The component (E) is (e1) a polymer having a liquid repellent group, or a specific surfactant described below.
[0062] <(e1) Liquid repellent group> (e1) The liquid repellent group may be, for example, at least one group selected from a fluoroalkyl group, a polyfluoroether group, a silyl ether group, and a polysiloxane group.
[0063] The fluoroalkyl group is preferably a fluoroalkyl group having 3 to 10 carbon atoms, and more preferably a fluoroalkyl group having 4 to 10 carbon atoms. Examples of such fluoroalkyl groups include a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2-(perfluorobutyl)ethyl group, a 3-perfluorobutyl-2-hydroxypropyl group, a 2-(perfluorohexyl)ethyl group, a 3-perfluorohexyl-2-hydroxypropyl group, a 2-(perfluorooctyl)ethyl group, a 3-perfluorooctyl-2-hydroxypropyl group, a 2-(perfluorodecyl)ethyl group, a 2-(perfluoro-3-methylbutyl)ethyl group, a 3-(perfluoro-3-methylbutyl)-2-hydroxypropyl group, a 2-(perfluoro-5-methylhexyl)ethyl group, a 2-(perfluoro-5-methylhexyl)-2-hydroxypropyl group, a 2-(perfluoro-7-methyloctyl)ethyl group, and a 2-(perfluoro-7-methyloctyl)-2-hydroxypropyl group.
[0064] The polyfluoroether group includes an Rf group having a polyfluoroether structure represented by the following formula (i). -(XO) n -Y (i) (In formula (i), X represents a divalent saturated hydrocarbon group having 1 to 10 carbon atoms which may have a fluorine atom, and each unit grouped by n represents the same or different groups; Y represents a hydrogen atom (only in the case where a fluorine atom is not bonded to the carbon atom adjacent to the oxygen atom adjacent to Y) or a monovalent saturated hydrocarbon group having 1 to 20 carbon atoms which may have a fluorine atom; and n represents an integer of 2 to 50, with the proviso that the total number of fluorine atoms in formula (i) is 2 or more.)
[0065] Preferred embodiments of X and Y in formula (i) include those in which X is an alkylene group having 1 to 10 carbon atoms in which one hydrogen atom has been substituted with a fluorine atom, or a perfluoroalkylene group having 1 to 10 carbon atoms, and each unit grouped by n represents the same or different groups, and Y is an alkyl group having 1 to 20 carbon atoms in which one hydrogen atom has been substituted with a fluorine atom, or a perfluoroalkyl group having 1 to 20 carbon atoms.
[0066] A more preferred embodiment of X and Y in formula (i) is one in which X is a perfluoroalkylene group having 1 to 10 carbon atoms, each unit grouped by n being the same or different, and Y is a perfluoroalkyl group having 1 to 20 carbon atoms.
[0067] In the Rf group represented by formula (i), n is preferably an integer of 2 to 50, more preferably an integer of 2 to 30, and even more preferably an integer of 2 to 15. When n is 2 or more, good liquid repellency is obtained. When n is 50 or less, when the polymer of component (E) is synthesized by copolymerization of a monomer having an Rf group with a monomer having a hydroxy group, a carboxy group, an amide group, an amino group, an N-alkoxymethylamide group, a blocked isocyanate group, or a trialkoxysilyl group, or with another monomer, the compatibility of the monomers is good.
[0068] In addition, in the Rf group represented by formula (i), the total number of carbon atoms is preferably 2 to 50, more preferably 2 to 30. Within this range, the polymer of component (E) exhibits good liquid repellency. In addition, when the polymer of component (E) is synthesized by copolymerizing a monomer having an Rf group with a monomer having a hydroxy group, a carboxy group, an amide group, an amino group, an N-alkoxymethylamide group, a blocked isocyanate group, or a trialkoxysilyl group, or with another monomer, the compatibility of the monomers is good.
[0069] Specific examples of X include, for example, -CF2-, -CF2CF2-, -CF2CF2CF2-, -CF2CF(CF3)-, -CF2CF2CF2CF2-, -CF2CF2CF(CF3)-, and CF2CF(CF3)CF2-.
[0070] Specific examples of Y include, for example, -CF3, -CF2CF3, -CF2CHF2, -(CF2)2CF3, -(CF2)3CF3, -(CF2)4CF3, -(CF2)5CF3, -(CF2)6CF3, -(CF2)7CF3, -(CF2)8CF3, -(CF2)9CF3, and (CF2) 11 CF3, -(CF2) 15 CF3 is an example.
[0071] A preferred embodiment of the Rf group represented by formula (i) is an Rf group represented by formula (ii). -C p-1 F 2(p-1) -O-(C p F 2p -O) n-1 -C q F 2q+1 (ii) (In formula (ii), p is 2 or 3 and is the same group for each unit grouped by n, q is an integer of 1 to 20, and n is an integer of 2 to 50.)
[0072] From the viewpoint of ease of synthesis, preferred specific examples of the Rf group represented by formula (ii) include the following groups. -CF2O(CF2CF2O) n-1CF3(n is 2 to 9) -CF(CF3)O(CF2CF(CF3)O) n-1 C6F 13 (n is 2 to 6) -CF(CF3)O(CF2CF(CF3)O) n-1 C3F7(n is 2 to 6)
[0073] The Rf groups in the polymer of component (E) may all be the same or different.
[0074] The silyl ether group means a group in which a hydroxy group of an alcohol is protected with a trialkylsilyl group, and is preferably a group represented by the following formula: -X 4 -Si(O-SiX 1 X 2 X 3 )3 (In the formula, X 1 , X 2 and X 3 each independently represents an alkyl group having 1 to 3 carbon atoms; X 4 represents an alkylene group having 1 to 6 carbon atoms.
[0075] The polysiloxane group may be a group having a polysiloxane structure represented by formula (iii). Hereinafter, the group having a polysiloxane structure represented by formula (iii) will be referred to as a pSi group. -(SiR a R b -O) m -SiR a R b R c (iii) (However, R a and R b each independently represents a hydrogen atom, an alkyl group, a cycloalkyl group, or an aryl group; R c represents a hydrogen atom or an organic group having 1 to 10 carbon atoms, and m represents an integer of 1 to 200.
[0076] R a and R bEach independently represents a hydrogen atom, an alkyl group, a cycloalkyl group, or an aryl group, and may be the same or different for each siloxy unit. Since the polymer of component (E) exhibits good liquid repellency, R a and R b are each independently a hydrogen atom, a methyl group, or a phenyl group, and further, R a and R b is preferably a methyl group. c may contain nitrogen atoms, oxygen atoms, and the like.
[0077] <(e2) At least one group selected from the group consisting of an N-alkoxymethylamide group, a blocked isocyanate group, and a trialkoxysilyl group> In the present invention, from the viewpoint of ink wettability at the openings of the subpixels, it is preferable that the compound further contains, in addition to the group (e1), at least one group selected from the group consisting of an N-alkoxymethylamide group, a blocked isocyanate group, and a trialkoxysilyl group.
[0078] Examples of the N-alkoxymethylamide group include an N-methoxymethyl(meth)acrylamide group, an N-ethoxymethyl(meth)acrylamide group, and an N-butoxymethyl(meth)acrylamide group.
[0079] The blocked isocyanate group is a group in which the blocking group is deprotected by heating to become an isocyanate group. Specific examples of the blocked isocyanate group include isocyanate groups substituted with alcohol, phenol, thioalcohol, imine, ketimine, amine, lactam, pyrazole, oxime, β-diketone, etc.
[0080] Examples of the trialkoxysilyl group include those shown below. -(CH2)2-Si(OCH3)3 -(CH2)3-Si(OCH3)3 -(CH2)2-Si(OCH2CH3)3 -(CH2)3-Si(OCH2CH3)3
[0081] <(e3) At least one group selected from the group consisting of a hydroxy group, a carboxy group, an amide group, and an amino group> In addition to the above (e1) and (e2) groups, from the viewpoint of ink wettability in the openings of the subpixels, it is preferable that the component (E) further includes (e3) at least one group selected from the group consisting of a hydroxy group, a carboxy group, an amido group, and an amino group.
[0082] <(e4) Acrylate group> The component (E) can also introduce an acrylate group that bonds via a urethane bond to a polymer having the above (e1) group. The acrylate group may be, for example, a (meth)acryloyl group, and can be introduced by reacting an acrylate having an isocyanate group with a polymer having a group (e1). Examples of acrylates having an isocyanate group include 2-(meth)acryloyloxyethyl isocyanate and 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate).
[0083] Examples of the polymer of component (E) include acrylic polymers, polyamic acids, polyimides, polyamides, polyureas, polyurethanes, phenolic resins, epoxy resins, polysiloxanes, and polyesters, each of which contains the above-mentioned group (e1), and optionally the group (e2), and further the group (e3). In the present invention, acrylic polymers are preferred.
[0084] [Acrylic polymer] The acrylic polymer can be obtained by polymerizing a monomer containing a group (e1), preferably by further copolymerizing it with a monomer containing a group (e2), more preferably by further copolymerizing it with a monomer containing a group (e3).
[0085] (e1) Monomer containing a liquid repellent group Examples of the monomer having a fluoroalkyl group include monomers having a fluoroalkyl group having 3 to 10 carbon atoms, such as 2,2,2-trifluoroethyl acrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, 2-(perfluorobutyl)ethyl methacrylate, 3-perfluorobutyl-2-hydroxypropyl ... -Perfluorobutyl-2-hydroxypropyl methacrylate, 2-(perfluorohexyl)ethyl acrylate, 2-(perfluorohexyl)ethyl methacrylate, 3-perfluorohexyl-2-hydroxypropyl acrylate, 3-perfluorohexyl-2-hydroxypropyl methacrylate, 2-(perfluorooctyl)ethyl acrylate, 2-(perfluorooctyl)ethyl methacrylate, 3-perfluorooctyl-2-hydroxypropyl acrylate, 3-perfluorooctyl-2-hydroxy Propyl methacrylate, 2-(perfluorodecyl)ethyl acrylate, 2-(perfluorodecyl)ethyl methacrylate, 2-(perfluoro-3-methylbutyl)ethyl acrylate, 2-(perfluoro-3-methylbutyl)ethyl methacrylate, 3-(perfluoro-3-methylbutyl)-2-hydroxypropyl acrylate, 3-(perfluoro-3-methylbutyl)-2-hydroxypropyl methacrylate, 2-(perfluoro-5-methylhexyl)ethyl acrylate, 2-(perfluoro-5-methylhexyl)ethyl perfluoro-7-methyloctyl)ethyl acrylate, 2-(perfluoro-5-methylhexyl)-2-hydroxypropyl acrylate, 2-(perfluoro-5-methylhexyl)-2-hydroxypropyl methacrylate, 2-(perfluoro-7-methyloctyl)ethyl acrylate, 2-(perfluoro-7-methyloctyl)ethyl methacrylate, 2-(perfluoro-7-methyloctyl)-2-hydroxypropyl acrylate, and 2-(perfluoro-7-methyloctyl)-2-hydroxypropyl methacrylate.
[0086] Examples of monomers having a silyl ether group include methacryloxypropyltris(trimethylsiloxy)silane and acryloxypropyltris(trimethylsiloxy)silane.
[0087] Examples of monomers having a polysiloxane group include CH2=CHCOO(pSi) and CH2=C(CH3)COO(pSi). Here, pSi represents a pSi group. The monomers having a pSi group may be used alone or in combination of two or more kinds.
[0088] When introducing a pSi group into the polymer of component (E), in addition to the above-mentioned method of copolymerizing a monomer having a pSi group, various modification methods in which a polymer having a reactive site is reacted with a compound having a pSi group, and a method using a polymerization initiator having a pSi group can also be used.
[0089] Examples of various modification methods for reacting a polymer having a reactive site with a compound having a pSi group include the following methods.
[0090] A method in which a monomer having an epoxy group is copolymerized in advance, and then a compound having a carboxy group at one end and a pSi group at the other end is reacted. A method in which a monomer having an epoxy group is copolymerized in advance, and then a compound having an amino group at one end and a pSi group at the other end is reacted. In this method, a monomer having an epoxy group is copolymerized in advance, and then a compound having a mercapto group at one end and a pSi group at the other end is reacted. In this method, a monomer having an amino group is copolymerized in advance, and then a compound having a carboxy group at one end and a pSi group at the other end is reacted with the copolymer.
[0091] In this method, a monomer having an amino group is copolymerized in advance, and then a compound having an epoxy group at one end and a pSi group at the other end is reacted with the copolymer. A method in which a monomer having a carboxy group is copolymerized in advance, and then a compound having an epoxy group at one end and a pSi group at the other end is reacted. A method in which a monomer having a carboxy group is copolymerized in advance, and then a compound having an amino group at one end and a pSi group at the other end is reacted. A method in which a monomer having a carboxy group is copolymerized in advance, and then a compound having a silyl chloride group at one end and a pSi group at the other end is reacted. A method in which a monomer having a hydroxyl group is copolymerized in advance, and then a compound having a silyl chloride group at one end and a PSi group at the other end is reacted.
[0092] The polymerization initiator having a pSi group may contain a group having a divalent polysiloxane structure in the molecular main chain, or may contain a group having a monovalent polysiloxane structure in the terminal portion or side chain of the initiator molecule. Examples of the polymerization initiator having a group having a divalent polysiloxane structure in the molecular main chain include compounds having a group having a divalent polysiloxane structure and an azo group alternately. Such polymerization initiators are easily available as commercial products, and examples thereof include VPS-1001 and VPS-0501 (both manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0093] (e2) A monomer containing a group selected from the group consisting of an N-alkoxymethylamide group, a blocked isocyanate group, and a trialkoxysilyl group. Examples of monomers having an N-alkoxymethylamide group include (meth)acrylamide compounds substituted with a hydroxymethyl group or an alkoxymethyl group, such as N-hydroxymethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-ethoxymethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide.
[0094] Examples of monomers having a blocked isocyanate group include 2-(0-(1'-methylpropylideneamino)carboxyamino)ethyl methacrylate and 2-(3,5-dimethylpyrazolyl)carbonylamino)ethyl methacrylate.
[0095] Examples of monomers having a trialkoxysilyl group include 3-trimethoxysilylpropyl acrylate, 3-triethoxysilylpropyl acrylate, 3-trimethoxysilylpropyl methacrylate, and 3-triethoxysilylpropyl methacrylate.
[0096] (e3) A monomer containing at least one group selected from the group consisting of a hydroxy group, a carboxy group, an amide group, and an amino group. Examples of monomers having a hydroxy group include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 2,3-dihydroxypropyl acrylate, 2,3-dihydroxypropyl methacrylate, glycerin monomethacrylate, diethylene glycol monoacrylate, diethylene glycol monomethacrylate, caprolactone 2-(acryloyloxy)ethyl ester, caprolactone 2-(methacryloyloxy)ethyl ester, and poly(ethylene glycol) acrylate. Examples of suitable hydroxyl groups include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 5-acryloyloxy-6-hydroxynorbornene-2-carboxylic-6-lactone, 5-methacryloyloxy-6-hydroxynorbornene-2-carboxylic-6-lactone, p-hydroxystyrene, α-methyl-p-hydroxystyrene, N-hydroxyphenylmaleimide, N-hydroxyphenylacrylamide, N-hydroxyphenylmethacrylamide, p-hydroxyphenylacrylate, and p-hydroxyphenylmethacrylate. Among these, 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate are preferred in the present invention.
[0097] Examples of monomers having a carboxy group include acrylic acid, methacrylic acid, crotonic acid, mono-(2-(acryloyloxy)ethyl)phthalate, mono-(2-(methacryloyloxy)ethyl)phthalate, N-(carboxyphenyl)maleimide, N-(carboxyphenyl)methacrylamide, and N-(carboxyphenyl)acrylamide.
[0098] Examples of monomers having an amide group include acrylamide, methacrylamide, N-methylacrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide. Among these, methacrylamide is preferred in the present invention.
[0099] Examples of monomers having an amino group include aminomethyl acrylate, aminomethyl methacrylate, 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 3-aminopropyl acrylate, and 3-aminopropyl methacrylate.
[0100] [Polyamic acid, polyimide] Examples of the polyamic acid include polyamic acids obtained by reacting diamines having a fluoroalkyl group with acid dianhydrides, and examples of the polyimides include polyimides obtained by imidizing the polyamic acids.
[0101] [polyamide] An example of the polyamide is a polyamide obtained by polymerizing a diamine having a fluoroalkyl group and a dicarboxylic acid anhydride.
[0102] [Polyurea] An example of the polyurea is a polyurea obtained by polymerizing a diamine having a fluoroalkyl group and a diisocyanate.
[0103] [Polyurethane] Examples of polyurethanes include polyurethanes obtained by polymerizing a diol having a fluoroalkyl group or a fluoroalkoxy group and a diol having an amino group with a diisocyanate.
[0104] [Phenol resin] An example of the phenol resin is a novolak resin obtained by polymerizing a phenol having a fluoroalkyl group or a fluoroalkoxy group with formaldehyde.
[0105] [Epoxy resin] Examples of epoxy resins include epoxy resins obtained by reacting either or both of bisphenol A and bisphenol F having a fluoroalkyl group or a fluoroalkoxy group with either or both of a diglycidyl ether of bisphenol A and a diglycidyl ether of bisphenol F.
[0106] [Polysiloxane] Examples of polysiloxanes include trialkoxysilanes having a fluoroalkyl group and dialkoxysilanes having a fluoroalkyl group. And and polysiloxanes obtained by polymerizing a silane monomer mixture containing an amino group-containing trialkoxysilane or an amino group-containing dialkoxysilane.
[0107] [polyester] Examples of the polyester include polyesters obtained by reacting a dicarboxylic acid or a tetracarboxylic dianhydride with a diol having a fluoroalkyl group or a fluoroalkoxy group.
[0108] The polymer of component (E) may further contain other monomers (hereinafter, other monomers E) in addition to the monomers having the groups (e1) to (e3) described above.
[0109] Specific examples of other monomers E include methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, benzyl methacrylate, naphthyl methacrylate, anthryl methacrylate, anthryl methyl methacrylate, phenyl methacrylate, glycidyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, methoxytriethylene glycol methacrylate, 2-ethoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, 3-methoxybutyl methacrylate, γ-butyrolactone methacrylate, 2-propyl-2-adamantyl methacrylate, 8-methyl-8-tricyclodecyl methacrylate, 8-ethyl-8-tricyclodecyl methacrylate, methyl acrylate, ethyl acrylate, isopropyl Examples of suitable acrylates include but are not limited to vinyl acrylate, benzyl acrylate, naphthyl acrylate, anthryl acrylate, anthryl methyl acrylate, phenyl acrylate, glycidyl acrylate, cyclohexyl acrylate, isobornyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, tetrahydrofurfuryl acrylate, 3-methoxybutyl acrylate, gamma-butyrolactone acrylate, 2-propyl-2-adamantyl acrylate, 8-methyl-8-tricyclodecyl acrylate, 8-ethyl-8-tricyclodecyl acrylate, N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, N-cyclohexylmaleimide, styrene, vinyl naphthalene, vinyl anthracene, and vinyl biphenyl.
[0110] In the polymer of component (E), the amount of the (e1) group introduced is preferably 5 to 60 mol %, more preferably 5 to 40 mol %, based on the total repeating units. By making the amount of the (e1) group introduced equal to or greater than the lower limit of the above range, good liquid repellency can be obtained. By making the amount of the (e1) group introduced equal to or less than the upper limit of the above range, problems such as aggregation are less likely to occur.
[0111] In the polymer of component (E), the amount of (e2) group selected from the group consisting of N-alkoxymethylamide group, blocked isocyanate group, and trialkoxysilyl group is preferably 5 to 70 mol %, more preferably 5 to 50 mol %, based on the total repeating units. By making the amount of (e2) group introduced equal to or greater than the lower limit of the above range, the obtained cured film has good heat resistance and solvent resistance. By making the amount of (e2) group introduced equal to or less than the upper limit of the above range, good developability is obtained.
[0112] When at least one group (e3) selected from the group consisting of a hydroxy group, a carboxy group, an amide group, and an amino group is introduced into the polymer of component (E), the amount of the group introduced is preferably 5 to 60 mol %, more preferably 5 to 40 mol %, based on all repeating units. By making the amount of the group (e3) introduced equal to or greater than the lower limit of the above range, the resulting cured film has good heat resistance and solvent resistance. By making the amount of the group (e3) introduced equal to or less than the upper limit of the above range, good liquid repellency is obtained.
[0113] The number average molecular weight Mn of the polymer of component (E) is preferably 2,000 to 100,000, more preferably 3,000 to 50,000, and even more preferably 4,000 to 10,000. When the Mn of the polymer of component (E) is equal to or less than the upper limit of the above range, residues are less likely to be generated. The number average molecular weight Mn of the polymer of component (E) is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0114] In the present invention, the polymer of component (E) may be a mixture of multiple types of copolymers.
[0115] The polymer of component (E) is obtained by polymerizing (e1) a monomer having a liquid repellent group, for example, a monomer having a fluoroalkyl group having 3 to 10 carbon atoms, a monomer having a polyfluoroether group, (e2) a monomer having at least one group selected from the group consisting of an N-alkoxymethylamide group, a blocked isocyanate group, and a trialkoxysilyl group, and (e3) a monomer having at least one group selected from the group consisting of a hydroxyl group, a carboxyl group, an amide group, and an amino group, as necessary, and other monomers E in a solvent in the presence of a polymerization initiator. The reaction temperature during polymerization can be appropriately set depending on the type of polymer to be produced, but when an acrylic polymer is produced, it is preferably set to 50 to 110°C. The solvent used in the polymerization reaction is not particularly limited as long as it dissolves the monomers used and the polymer to be obtained. Specific examples of the solvent include the solvents described in (F) solvent below.
[0116] The above component (E) is usually obtained as a solution, but if necessary, it may be isolated or purified by the same method as described in the description of component (A). The polymerization solution of the copolymer of component (E) may be used as is, or a solution obtained by redissolving the isolated polymer powder in a suitable solvent may be used. Examples of the solvent include the solvents exemplified in component (F) described below.
[0117] Examples of the surfactant of component (E) include fluorine-based surfactants, silicone-based surfactants, and nonionic surfactants. These surfactants are also available as commercial products, such as Polyfox PF-136A, 151, 156A, 154N, 159, 636, 6320, 656, and 6520 (manufactured by Omnova), Megafac (registered trademark) R30, R08, R40, R41, R43, F251, F477, F552, F553, F554, F555, F556, F 557, F558, F559, F560, F561, F562, F563, F565, F567, F570 (manufactured by DIC Corporation), FC4430, FC4432 (manufactured by Sumitomo 3M Limited), Asahiguard (registered trademark) AG710, Surflon (registered trademark) S-386, S-611, S-651 (manufactured by AGC Seimi Chemical Co., Ltd.), Futergent (registered trademark) FTX-218, D Fluorosurfactants such as FX-18, 220P, 251, 212M, and 215M (manufactured by Neos Co., Ltd.); BYK-300, 302, 306, 307, 310, 313, 315, 320, 322, 323, 325, 330, 331, 333, 342, 345, 346, 347, 348, 349, 370, 377, 378, and 3455 (manufactured by BYK Japan Co., Ltd.), SH3746, Examples of such silicone surfactants include SH3749, SH3771, SH8400, SH8410, SH8700, SF8428 (manufactured by Toray Dow Corning Silicone Co., Ltd.), KF-351, KF-352, KF-353, KF-354L, KF-355A, KF-615A, KF-945, KF-618, KF-6011, and KF-6015 (manufactured by Shin-Etsu Chemical Co., Ltd.). These surfactants may be used alone or in combination of two or more.
[0118] The content of the component (E) is preferably 0.5 to 10 parts by mass, and more preferably 1 to 5 parts by mass, based on 100 parts by mass of the component (A). When the content of the component (E) is within the above range, good liquid repellency is obtained, and it is also preferable from an economical point of view.
[0119] <(F) Component: Solvent> The solvent for component (F) is not particularly limited in type or structure, so long as it dissolves components (A), (B), and (C) and also dissolves component (G) (described below) that is added as necessary.
[0120] As the solvent for component (F), a solvent generally used in photoresist materials can be used, such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol propyl ether, propylene glycol propyl ether acetate, toluene, xylene, methyl ethyl ketone, cyclopentanone, cyclohexyl ether, butyl ... Sanon, 2-butanone, 3-methyl-2-pentanone, 2-pentanone, 2-heptanone, γ-butyrolactone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxyacetate, ethyl hydroxyacetate, methyl 2-hydroxy-3-methylbutanoate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. In the present invention, among these, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl lactate, and butyl lactate are preferred, taking into consideration the coatability and safety of the composition. These solvents can be used alone or in combination of two or more.
[0121] <(G) component> The component (G) is a thiol compound, which is added for the purpose of improving the curing speed of the resin composition, as long as the effect of the present invention is not impaired.
[0122] The thiol compound of the component (G) is not particularly limited, and examples thereof include 1-hexanethiol, 1-heptanethiol, 1-octanethiol, 1-nonanethiol, 1-decanethiol, 1-undecanethiol, 1-dodecanethiol, 1-octadecanethiol, 2-mercaptobenzothiazole, 6-methyl-2-mercaptobenzothiazole, 5-chloro-2-mercaptobenzothiazole, 2-naphthalenethiol, 2,5-dimercapto-1,3,4-thiadiazole, 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercapto propionate, stearyl-3-mercaptopropionate, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]isocyanurate, pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutanate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and 1,3,5-tris[2-(3-sulfanylbutanoyloxy)ethyl]-1,3,5-triazinane-2,4,6-trione. Among these, in the present invention, from the viewpoint of high storage stability of the resin composition and sufficient curability, pentaerythritol tetrakis(3-mercaptobutanate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and 1,3,5-tris[2-(3-sulfanylbutanoyloxy)ethyl]-1,3,5-triazinane-2,4,6-trione are preferred. These thiol compounds can be used alone or in combination of two or more.
[0123] When the (G) component is used, its content is preferably 0.01 to 10 parts by mass, more preferably 0.03 to 5 parts by mass, based on 100 parts by mass of the (A) component. When the (G) component content is equal to or greater than the lower limit of the above range, the curability is improved. When the (G) component content is equal to or less than the upper limit of the above range, the pattern resolution is improved.
[0124] <(H) component> The component (H) is an adhesion promoter. The resin composition of the present invention may be added with an adhesion promoter for the purpose of improving adhesion to a substrate after development. Specific examples of such adhesion promoters include chlorosilanes such as trimethylchlorosilane, dimethylvinylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane; trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylvinylethoxysilane, diphenyldimethoxysilane, phenyltriethoxysilane, vinyltrichlorosilane, γ-aminopropyltriethoxysilane, γ-methacryloyloxypropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-(N-piperidinyl)propyltriethoxysilane, 3-urea Examples of the adhesion promoter include alkoxysilanes such as 3-ureidopropyltriethoxysilane and 3-ureidopropyltrimethoxysilane; silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine and trimethylsilylimidazole; heterocyclic compounds such as benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, urazole, thiouracil, mercaptoimidazole and mercaptopyrimidine; urea compounds such as 1,1-dimethylurea; and thiourea compounds such as 1,3-dimethylurea. In the present invention, among these, alkoxysilanes (i.e., silane coupling agents) are preferred in that good adhesion can be obtained. In addition, these adhesion promoters can be used alone or in combination of two or more.
[0125] The adhesion promoter may be, for example, a commercially available compound manufactured by Shin-Etsu Chemical Co., Ltd., Momentive Performance Materials Worldwide Inc., or Dow Corning Toray Silicones Co., Ltd., and these commercially available products are easily available.
[0126] When the (H) component is blended, its content is usually 0.1 to 20 parts by mass, preferably 0.5 to 10 parts by mass, per 100 parts by mass of the (A) component. By making the content of the (H) component equal to or less than the upper limit of the above range, good sensitivity can be obtained. By making the content of the (H) component equal to or more than the lower limit of the above range, sufficient effect of the adhesion promoter can be obtained.
[0127] <Other additives> Furthermore, the resin composition of the present invention may contain, as necessary, a sensitizer, a chain transfer agent, a crosslinking agent, a rheology modifier, a pigment, a dye, a storage stabilizer, an antifoaming agent, or a dissolution promoter such as a polyhydric phenol or a polyvalent carboxylic acid, as long as the effects of the present invention are not impaired.
[0128] <Resin composition> The resin composition of the present invention is a composition obtained by dissolving or dispersing, in a solvent (F), an alkali-soluble polymer (A), a compound having two or more polymerizable groups (B), a photoinitiator (C-1) having an oxime ester group and having an absorption coefficient at 365 nm in methanol or acetonitrile of 5,000 ml / g cm or more, a black pigment (D), and a liquid-repellent component (E), and may further contain, as necessary, one or more of a photoinitiator (C-2), a thiol compound (G), an adhesion promoter (H), and other additives.
[0129] Preferred embodiments of the resin composition of the present invention include, but are not limited to, those shown below. [1]: A resin composition in which 100 parts by mass of the (A) component, 10 to 150 parts by mass of the (B) component, 0.3 to 5 parts by mass of the (C-1) component, 1 to 50 parts by mass of the (D) component, and the (E) component are dissolved or dispersed in a solvent for the (F) component. [2]: A resin composition comprising the above composition [1], and containing 0.5 to 10 parts by mass of the component (E) per 100 parts by mass of the component (A). [3]: The resin composition according to the above [1] or [2], further comprising 0.01 to 10 parts by mass of a component (G) per 100 parts by mass of the component (A). [4]: The resin composition according to the above [1], [2] or [3], further comprising 0.1 to 20 parts by mass of component (H) per 100 parts by mass of component (A). [5]: A resin composition, further comprising, in any one of the compositions [1] to [4] above, 0.5 to 10 parts by mass of a component (C-2) per 100 parts by mass of the component (A).
[0130] The solid content concentration in the resin composition of the present invention is not particularly limited as long as each component is uniformly dissolved or dispersed in the solvent, but is preferably 1 to 80 mass%, more preferably 5 to 70 mass%, and even more preferably 10 to 60 mass%. Here, the solid content refers to the total amount of components other than the solvent that constitute the resin composition.
[0131] The method for preparing the resin composition of the present invention is not particularly limited, but examples of the preparation method include a method in which the copolymer of component (A) is dissolved in the solvent of component (F), and the compound having two or more polymerizable groups of component (B), the photoinitiator of component (C-1), the black pigment of component (D), and the liquid-repellent component of component (E) are mixed with this solution in a predetermined ratio; or a method in which, at an appropriate stage of this preparation method, the photoinitiator of component (C-2), the thiol compound of component (G), the adhesion promoter of component (H), and other additives are further added as necessary.
[0132] In preparing the resin composition of the present invention, the polymerization solution of the copolymer of component (A) obtained by the polymerization reaction in the solvent of component (F) can be used as is. In this case, when the polymerization solution of component (A) is mixed with components (B), (C-1), and (D) as described above, the solvent of component (F) may be added for the purpose of adjusting the concentration. In this case, the solvent of component (F) used in the process of forming the copolymer of component (A) and the solvent of component (F) used for adjusting the concentration during the preparation of the resin composition may be the same or different.
[0133] The resin composition obtained above can be used as is for pattern formation, but it is preferable to use the composition after filtering through a filter having a pore size of about 1.0 μm.
[0134] <Coating film and cured film> The resin composition of the present invention can be applied to a substrate such as a suitable substrate (e.g., a silicon / silicon dioxide-coated substrate, a silicon nitride substrate, a substrate coated with a metal such as aluminum, molybdenum, or chromium, a glass substrate, a quartz substrate, or an ITO substrate) or a film (e.g., a triacetyl cellulose film, a cycloolefin polymer film, a cycloolefin copolymer film, a polyethylene terephthalate film, a polyester film, an acrylic film, or a polyimide resin film) by a method such as spin coating, flow coating, roll coating, slit coating, slit coating followed by spin coating, or an inkjet method, and then pre-dried on a hot plate or in an oven, to form a coating film. The coating film is then heat-treated (pre-baked) to form a negative-type photosensitive resin film having photosensitivity.
[0135] The above pre-drying is not particularly limited as long as it can remove the solvent contained in the composition and does not adversely affect the coating film, and may be natural drying, heat drying using a hot plate or an oven, etc. The pre-drying may be performed integrally with pre-baking.
[0136] The pre-baking conditions are generally preferably 60 to 150° C., more preferably 80 to 120° C., and are performed for 0.5 to 30 minutes when using a hot plate, or for 0.5 to 90 minutes when using an oven.
[0137] The thickness of the negative photosensitive resin film formed from the above resin composition is preferably 0.1 to 50 μm, more preferably 0.5 to 40 μm, even more preferably 1 to 30 μm, and most preferably 5 to 20 μm.
[0138] When the negative photosensitive resin film formed from the resin composition of the present invention is exposed to light such as ultraviolet light, ArF, KrF, or F2 laser light using a mask having a predetermined pattern, the exposed area of the film becomes insoluble in an alkaline developer due to the action of radicals generated from the photopolymerization initiators of components (C-1) and (C-2) contained in the negative photosensitive resin film.
[0139] In the present invention, in consideration of sufficient curing deep into the film, it is preferable to use ultraviolet light as the irradiating light, and it is more preferable to use ultraviolet light with a wavelength of 365 nm.
[0140] Then, development is performed using an alkaline developer, which removes the unexposed portions of the negative photosensitive resin film, forming a pattern-like relief.
[0141] Examples of alkaline developers that can be used in the present invention include aqueous solutions of alkali metal hydroxides such as sodium carbonate, potassium carbonate, potassium hydroxide, and sodium hydroxide; aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine. Furthermore, surfactants and the like can be added to these developers.
[0142] Examples of developers that are commonly used for photoresists include a 0.5 to 3 mass % aqueous sodium carbonate solution, a 0.01 to 0.5 mass % aqueous potassium hydroxide solution, and a 0.1 to 2.38 mass % aqueous tetraethylammonium hydroxide solution. By using such an alkaline developer in the resin composition of the present invention, good development can be achieved without causing problems such as swelling.
[0143] The developing method may be any of spraying, puddling, dipping, and swing immersion, etc. The developing time is usually 15 to 200 seconds.
[0144] After development, the negative photosensitive resin film is washed with running water. The washing time is not particularly limited as long as the developer can be sufficiently removed, but is usually 20 to 90 seconds. After washing, the film may be air-dried using compressed air or compressed nitrogen, or by spinning. The moisture on the substrate is removed, and a patterned film is obtained.
[0145] Subsequently, the obtained pattern-forming film is post-baked for thermal curing or post-exposed for photocuring, specifically by heating using a hot plate or oven, or exposing using an ultraviolet irradiation device, to obtain a film (cured film) having a good relief pattern with improved heat resistance, flattening properties, low water absorption, chemical resistance, etc.
[0146] The post-baking conditions are generally preferably 150 to 300° C., more preferably 200 to 250° C., and are preferably heated for 1 to 30 minutes when using a hot plate, or for 1 to 90 minutes when using an oven. In the present invention, by carrying out such post-baking, a cured film having a desired good pattern shape can be obtained.
[0147] As described above, the resin composition according to the present invention has a relatively high transmittance of ultraviolet light in the exposure step, can be sufficiently cured deep into the film, and can form a cured film with high visible light blocking properties by curing the composition. The obtained cured film can be suitably used as a material for self-luminous displays such as QD-OLED displays and micro LED displays, and can contribute to further improving the image quality by using it as a partition (colored partition) constituting a subpixel of a wavelength conversion layer of a self-luminous display panel. EXAMPLES
[0148] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0149] [Abbreviations used in the Examples] The abbreviations used in the following examples have the following meanings. MAA: Methacrylic acid MMA: Methyl methacrylate AIBN: Azobisisobutyronitrile PRG1: Ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime) (365 nm absorption coefficient: 7,749 ml / g cm in CH3CN) PRG2: 1-Hydroxy-cyclohexyl-phenyl-ketone (365 nm extinction coefficient: 88.64 ml / g cm in MeOH) PRG3: BASF IRGACURE (registered trademark) OXE03 DPHA: KAYARAD (registered trademark) DPHA (product name), manufactured by Nippon Kayaku Co., Ltd., a mixture of dipentaerythritol penta- and hexaacrylates A-DPH-12E: NK Ester (registered trademark) A-DPH-12E (product name), ethoxylated dipentaerythritol hexaacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd. CTA: Karenz-MT (registered trademark) PE1 (product name), pentaerythritol tetrakis (3-mercaptobutyrate), manufactured by Showa Denko K.K. PFHMA: 2-(perfluorohexyl)ethyl methacrylate KBM-503: 3-Methacryloxypropyltriethoxysilane (also known as 3-triethoxysilylpropyl acrylate) HEMA: 2-hydroxyethyl methacrylate PFPE1: Perfluoropolyether having two hydroxyl groups at each end without a poly(oxyalkylene) group [Fomblin (registered trademark) T4, manufactured by Solvay Specialty Polymers] BEI: 1,1-bis(acryloyloxymethyl)ethyl isocyanate [Karenz (registered trademark) BEI, manufactured by Showa Denko K.K.] DOTDD: Dioctyltin dineodecanoate [Neostan (registered trademark) U-830, manufactured by Nitto Kasei Co., Ltd.] PGME: Propylene glycol monomethyl ether MEK: Methyl ethyl ketone
[0150] [Black pigment and dispersant] Black pigment 1: NITRBLACK UB-1, manufactured by Mitsubishi Materials Corporation Black pigment 2: Mitsubishi Materials Corporation, 13M-T Dispersant: Solsperse 34750, manufactured by Lubrizol Japan Co., Ltd.
[0151] <Light transmittance of thin films containing black pigment> (1) Formation of a thin film containing black pigment 1 P1 (8.11 g), DPHA (1.99 g), PRG1 (0.03 g), PRG2 (0.09 g), CTA (0.01 g), pigment dispersion 1 (0.63 g), P2 (0.50 g), and PGME (0.65 g) obtained in Synthesis Example 1 described later were mixed to prepare a dispersion (black pigment 1-containing resin composition) in which component (D) was dispersed in component (F) at a ratio of 10 parts by mass to 100 parts by mass of component (A). The obtained dispersion was applied to alkali-free glass (substrate) using a spin coater, and then prebaked on a hot plate at 100 ° C. for 120 seconds to form a black pigment 1-containing thin film having a thickness of 10 μm.
[0152] (2) Formation of a thin film containing black pigment 2 A dispersion (black pigment 2-containing resin composition) in which component (D) was dispersed in component (F) at a ratio of 10 parts by mass to 100 parts by mass of component (A) was prepared in the same manner as in (1), except that pigment dispersion 2 described below was used instead of pigment dispersion 1 used in (1). Using the obtained dispersion, a black pigment 2-containing thin film having a thickness of 10 μm was formed on non-alkali glass (substrate) in the same manner as in (1).
[0153] (3) Measurement of light transmittance The thin film formed above was measured for transmittance T1 at a wavelength of 365 nm and transmittance T2 at a wavelength of 550 nm using an ultraviolet-visible spectrophotometer (Shimadzu UV-2550 model, manufactured by Shimadzu Corporation), and the ratio of the two, T1 / T2, was calculated. The results are shown in Table 1.
[0154] [Table 1]
[0155] [Measurement of number average molecular weight Mn and weight average molecular weight Mw of component (A) and component (E)] The Mn and Mw of the copolymer of component (A), component (E) and polymer of component (E) synthesized according to the following synthesis examples were measured using a GPC apparatus (columns KF803L and KF804L) manufactured by Shimadzu Science Co., Ltd., under the condition that tetrahydrofuran was passed through the column as an elution solvent at a flow rate of 1 mL / min (column temperature 40° C.) to elute. The following number average molecular weight (hereinafter referred to as Mn) and weight average molecular weight (hereinafter referred to as Mw) are expressed in terms of polystyrene.
[0156] <Synthesis Example 1> As the monomer components constituting the copolymer, MAA (30.0 g) and MMA (120.0 g) were used, and AIBN (6.4 g) was used as a radical polymerization initiator. These were polymerized in PGME (290 g) as a solvent at 60 to 90°C for 16 hours to obtain a copolymer solution P1 (copolymer concentration: 35% by mass) of component (A). The Mn of the obtained copolymer was 9,700 and the Mw was 21,500.
[0157] <Synthesis Example 2> PFHMA (5.00 g), KBM-503 (3.83 g), and HEMA (1.51 g) were used as monomer components constituting the copolymer, and AIBN (0.52 g) was used as a radical polymerization initiator. These were polymerized in PGME (25.32 g) as a solvent at 80°C for 16 hours to obtain copolymer solution P2 (copolymer concentration: 30% by mass) of component (E). The Mn of the obtained copolymer was 4,800 and Mw was 6,700.
[0158] <Synthesis Example 3> PFPE1 (1.19 g), BEI (0.48 g), and DOTDD (0.017 g) were used as a catalyst, and reacted in MEK (1.67 g) as a solvent at room temperature (approximately 23° C.) for 24 hours to obtain a polymer solution P3 (polymer concentration: 50% by mass) of component (E). The Mn of the obtained P3 was 2,500 and the Mw was 3,000.
[0159] <Preparation of pigment dispersion> The black pigment, solvent, and dispersant were mixed in the proportions shown in Table 2. This solution was subjected to dispersion treatment for 8 hours using a mix rotor. Zirconia beads with a diameter of 0.5 mm were used as the beads, and five times the mass of the dispersion liquid was added. After dispersion was completed, the beads and the dispersion liquid were separated using a filter to prepare a pigment dispersion liquid.
[0160] [Table 2]
[0161] <Examples 1 to 3, Comparative Examples 1 to 2> According to the formulation shown in Table 3 below, a solution of component (A) was mixed with component (B), component (C-1), a solvent for component (F), optional components, component (D), and component (E), and the mixture was stirred at room temperature for 3 hours to prepare resin compositions of the examples and comparative examples.
[0162] [Table 3]
[0163] For each of the obtained resin compositions of Examples 1 to 3 and Comparative Examples 1 and 2, the transmittance was measured and the pattern shape was observed.
[0164] [Evaluation of transmittance and optical density (OD value)] The resin composition was applied onto alkali-free glass (substrate) using a spin coater, and then prebaked on a hot plate at 100°C for 120 seconds to form a coating film (film thickness 14 µm). The resulting coating film was irradiated with a UV irradiator PLA-600FA manufactured by Canon Inc. at a light intensity of 5.5 mW / cm at 365 nm. 2 UV rays of 140mJ / cm 2 After that, spray development was performed with a 0.033% by mass aqueous solution of potassium hydroxide for 180 seconds, and then washing was performed with running ultrapure water for 30 seconds. Next, the coating film was post-baked by heating it at 230°C for 30 minutes in an oven to obtain a cured film (film thickness 10 μm).
[0165] The cured film obtained above was measured for transmittance at wavelengths of 200 to 800 nm using an ultraviolet-visible spectrophotometer (Shimadzu UV-2550 model, manufactured by Shimadzu Corporation) and the optical density at 550 nm (OD value) was calculated. The OD value is a value that indicates the light-shielding ability, and the higher the value, the higher the light-shielding ability. The results are shown in Table 3.
[0166] [Evaluation of patterning] The resin composition was applied onto alkali-free glass (substrate) using a spin coater, and then prebaked on a hot plate at 100° C. for 120 seconds to form a coating film (film thickness 14 μm). This coating film was irradiated with ultraviolet light at 365 nm using a Canon Inc. PLA-600FA ultraviolet irradiator through a 10 μm line and space pattern mask at a light intensity of 5.5 mW / cm. 2 UV rays of 140mJ / cm 2 The coating was then irradiated with light. Thereafter, spray development was performed with a 0.033% by mass aqueous solution of potassium hydroxide for 180 seconds, and then washing was performed with running ultrapure water for 30 seconds. Next, the coating was post-baked and cured by heating at 230°C for 30 minutes using an oven. The cross-sectional shape of the cured line and space pattern was observed using a scanning electron microscope S-4800 manufactured by Hitachi High-Technologies Corporation, and the resolution of the pattern was evaluated according to the following criteria. The results are shown in Table 4. Evaluation Criteria ○: Pattern formation possible, no residual film ×: Pattern formation is not possible, or pattern formation is possible but there is a residual film
[0167] [Table 4]
[0168] From the results in Table 4, excellent properties such as excellent visible light shielding property and good resolution were exhibited in Examples 1 to 3. On the other hand, the visible light shielding property was insufficient in Comparative Example 1, and a pattern could not be formed in Comparative Example 2.
Claims
1. (A) an alkali-soluble copolymer, (B) a compound having two or more polymerizable groups of at least one type selected from the group consisting of an acrylate group, a methacrylate group, a vinyl group, and an allyl group; (C) Photoinitiator: (C-1) a photoinitiator having an oxime ester group and having an absorption coefficient in methanol or acetonitrile of 5,000 ml / g cm or more at 365 nm, (D) black pigment: a dispersion containing components (A), (B), (C-1), (C-2) a photoinitiator having an absorption coefficient in methanol or acetonitrile of 100 ml / g cm or less at 365 nm, (D) a black pigment, (E) a liquid-repellent component, (F) a solvent, and (G) a thiol compound, the dispersion being obtained by dispersing 10 parts by mass of component (D) in component (F) relative to 100 parts by mass of component (A), and coating the dispersion on a glass substrate and drying to form a thin film having a thickness of 10 μm, the light transmittance at a wavelength of 365 nm being T 1 , the light transmittance at a wavelength of 550 nm is T 2 Then, T 1 / T 2 a black pigment having a value of 1.0 or more and 5.0 or less, the black pigment being zirconium nitride, titanium nitride, titanium oxynitride, a mixed powder containing zirconium nitride and titanium nitride, or a mixed powder containing zirconium nitride and titanium oxynitride; (E) a liquid-repellent component, and (F) Solvent and does not contain, as a black pigment, an organic black pigment which is a compound represented by the following general formula (X), a geometric isomer of the compound, a salt of the compound, or a salt of a geometric isomer of the compound: 【Chemistry 1】 (In formula (X), R 1a and R 6 are each independently a hydrogen atom, CH 3 , C.F. 3 , a fluorine atom or a chlorine atom; R 2a , R 3 , R 4 , R 5 , R 7 , R 8 , R 9 and R 10 are each independently a hydrogen atom, a halogen atom, R 11 , COOH, COOR 11 , COO - , C.O.N.H. 2 , C.O.N.R. 11 , C.O.R. 11 R 12 , C.N., O.H., O.R. 11 , COCR 11 , O.O.C.N.H. 2 , OOCNHR 11 , OOCNR 11 R 12 , NO 2 , N.H. 2 , N.H.R. 11 , N.R. 11 R 12 , NHCOR 12 , N.R. 11 C.O.R. 12 , N=CH 2 , N=CHR 11 , N=CR 11 R 12 , S.H., S.R. 11 , S.O.R. 11 , S.O. 2 R 11 , S.O. 3 R 11 , S.O. 3 H, SO 3 - , S.O. 2 N.H. 2 , S.O. 2 NHR 11 or S.O. 2 N.R. 11 R 12 is; And R 2a and R 3 , R 3 and R 4 , R 4 and R 5 , R 7 and R 8 , R 8 and R 9 , and R 9 and R 10 At least one combination selected from the group consisting of: 11 They may also be joined together by bridges; R 11 and R 12 are each independently an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, or an alkynyl group having 2 to 12 carbon atoms.
2. 2. The resin composition according to claim 1, wherein the content of the component (D) is 1 to 50 parts by mass per 100 parts by mass of the component (A).
3. 3. The resin composition according to claim 1, wherein the number average molecular weight of component (A) is 2,000 to 50,000 in terms of polystyrene.
4. 4. The resin composition according to claim 1, wherein the component (A) is a copolymer of a monomer mixture containing at least one member selected from the group consisting of acrylic acid, methacrylic acid, maleic anhydride, and maleimide.
5. The resin composition according to any one of claims 1 to 4, wherein the content of the component (C-1) is 0.3 to 5 parts by mass per 100 parts by mass of the component (A).
6. 6. The resin composition according to claim 1, wherein the content of the component (B) is 10 to 150 parts by mass per 100 parts by mass of the component (A).
7. 7. The resin composition according to claim 1, wherein the component (C-1) is a photoinitiator having a carbazole structure.
8. A resin composition according to any one of claims 1 to 7, further comprising (G) a thiol compound.
9. The resin composition according to claim 8, wherein the component (G) is one or more selected from the group consisting of pentaerythritol tetrakis(3-mercaptobutanate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and 1,3,5-tris[2-(3-sulfanylbutanoyloxy)ethyl]-1,3,5-triazinane-2,4,6-trione.
10. The resin composition according to claim 1, wherein the value of T 1 / T 2 is 1.5 or more.
11. The resin composition according to claim 1, wherein the value of T 1 / T 2 is 3.0 or less.
12. A cured film obtained from the resin composition according to any one of claims 1 to 11.
13. A partition wall for a self-luminous display formed from the resin composition according to any one of claims 1 to 11.
14. A wavelength conversion layer of a self-luminous display comprising the partition wall according to claim 13.
15. An organic electroluminescence device comprising the wavelength conversion layer according to claim 14.
16. A micro LED device comprising the wavelength conversion layer of claim 14.
Citation Information
Patent Citations
Color filter
JP1991274503A
Curable composition for optical nanoimprint, curing material and method for manufacturing it
JP2010114209A
Mixed powder for forming black film and manufacturing method therefor
JP2018083730A
Coloring photosensitive resin composition, cured product, organic electroluminescenct element, image display device, and illumination
JP2018155878A
Photosensitive resin composition and method for manufacturing substrate with resin film
JP2019070720A